2018
DOI: 10.1016/j.immuni.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Interferon-γ Causes Insulin Resistance in Skeletal Muscle and Derails Glycemic Control in Obesity

Abstract: Pro-inflammatory cytokines of a T helper-1-signature are known to promote insulin resistance (IR) in obesity, but the physiological role of this mechanism is unclear. It is also unknown whether and how viral infection induces loss of glycemic control in subjects at risk for developing diabetes mellitus type 2 (DM2). We have found in mice and humans that viral infection caused short-term systemic IR. Virally-induced interferon-γ (IFN-γ) directly targeted skeletal muscle to downregulate the insulin receptor but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
158
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 160 publications
(180 citation statements)
references
References 70 publications
(73 reference statements)
8
158
0
1
Order By: Relevance
“…Similarly, people with acute mild respiratory infection showed higher insulin levels, but similar blood glucose levels at time of diagnosis compared to a time point three months later . In mice, infection with cytomegalovirus (CMV), lymphochriomeningitis virus (LCMV) or mild influenza, induced systemic insulin resistance, whereas it did not lead to a loss of glycemic control . In lean people and mice, infection‐induced IR is compensated by increased insulin output by the pancreas, which prevents fasting and postprandial hyperglycemia .…”
Section: Regulation Of Blood Glucose Levels During Infectionmentioning
confidence: 97%
See 3 more Smart Citations
“…Similarly, people with acute mild respiratory infection showed higher insulin levels, but similar blood glucose levels at time of diagnosis compared to a time point three months later . In mice, infection with cytomegalovirus (CMV), lymphochriomeningitis virus (LCMV) or mild influenza, induced systemic insulin resistance, whereas it did not lead to a loss of glycemic control . In lean people and mice, infection‐induced IR is compensated by increased insulin output by the pancreas, which prevents fasting and postprandial hyperglycemia .…”
Section: Regulation Of Blood Glucose Levels During Infectionmentioning
confidence: 97%
“…An analysis of patients infected with HIV showed increased insulin levels, whereas fasting plasma glucose levels (FPG) were not different from those of age and gender‐matched controls . Similarly, people with acute mild respiratory infection showed higher insulin levels, but similar blood glucose levels at time of diagnosis compared to a time point three months later . In mice, infection with cytomegalovirus (CMV), lymphochriomeningitis virus (LCMV) or mild influenza, induced systemic insulin resistance, whereas it did not lead to a loss of glycemic control .…”
Section: Regulation Of Blood Glucose Levels During Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anabolic demands imposed by the induction of resistance mechanisms are mainly satisfied by glucose [14], which is prioritized to immune cells inducing a robust and long-lasting insulin-resistant state in glucose-utilizing pathways of peripheral tissues [15]. Moreover, it has been recently shown that INF-γ released in the course of viral immunity targets skeletal muscle cells to downregulate the insulin receptor, driving compensatory hyperinsulinemia, which boosts glucose uptake by CD8 T cells and sustains antiviral cytotoxic resistance responses [16]. As different parenchymal tissues encounter different types of stress, damage and functional impairment during infection, disease physiology is uniquely context specific and so are the metabolic adaptations that promote tolerance.…”
Section: Metabolic Substrates Utilization and Disease Tolerancementioning
confidence: 99%